Mengoptimalkan Kontak Kultur dan Pengalaman Menyenangkan Wisatawan untuk Meningkatkan Citra Destinasi dan Bauran Pemasaran pada Pantai Oetune - Engelbertus G. Ch. Watu (AKSIOMA : Jurnal Manajemen, 2025)
In sustaining a destination in the competitive tourism sector, cultural contact and enjoyable tourism experiences must be utilized. This study explores their impact on destination image and marketing mix (7Ps) at Oetune Beach, South Central Timor Regency, Indonesia. Findings from a quantitative explanatory study based on data collected from 126 tourists indicate that cultural contact and positive tourism experiences both significantly enhance destination image and marketing mix effectiveness. This study emphasizes the importance of local stakeholders to formally initiate these dimensions in the marketing mix so that they can be more competitive and satisfy their visitors. The findings provide actionable insights for destination management to create sustainable tourism development and long-term success.